Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Consider the function [tex]\( h(x) = (g \circ f)(x) = \frac{1}{(x+3)^2} \)[/tex].
We need to find the correct decomposition of [tex]\( h(x) \)[/tex] into functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that [tex]\( h(x) = g(f(x)) \)[/tex].
Let's test each option one by one:
### Option A:
- [tex]\( f(x) = \frac{1}{x} \)[/tex]
- [tex]\( g(x) = x+3 \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g\left(\frac{1}{x}\right) = \left(\frac{1}{x}\right) + 3 \][/tex]
[tex]\[ g(f(x)) \neq \frac{1}{(x+3)^2} \][/tex]
Therefore, Option A is incorrect.
### Option B:
- [tex]\( f(x) = \frac{1}{x^2} \)[/tex]
- [tex]\( g(x) = x+3 \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g\left(\frac{1}{x^2}\right) = \left(\frac{1}{x^2}\right) + 3 \][/tex]
[tex]\[ g(f(x)) \neq \frac{1}{(x+3)^2} \][/tex]
Therefore, Option B is incorrect.
### Option C:
- [tex]\( f(x) = x^2 \)[/tex]
- [tex]\( g(x) = x+3 \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g\left(x^2\right) = \left(x^2\right) + 3 \][/tex]
[tex]\[ g(f(x)) \neq \frac{1}{(x+3)^2} \][/tex]
Therefore, Option C is incorrect.
### Option D:
- [tex]\( f(x) = x+3 \)[/tex]
- [tex]\( g(x) = \frac{1}{x^2} \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g(x+3) = \frac{1}{(x+3)^2} \][/tex]
[tex]\[ g(f(x)) = \frac{1}{(x+3)^2} \][/tex]
This matches the given function [tex]\( h(x) \)[/tex].
Therefore, the correct possible decomposition of [tex]\( h(x) \)[/tex] is:
[tex]\[ \boxed{f(x) = x+3, \ g(x) = \frac{1}{x^2}} \][/tex]
The correct option is D.
We need to find the correct decomposition of [tex]\( h(x) \)[/tex] into functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that [tex]\( h(x) = g(f(x)) \)[/tex].
Let's test each option one by one:
### Option A:
- [tex]\( f(x) = \frac{1}{x} \)[/tex]
- [tex]\( g(x) = x+3 \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g\left(\frac{1}{x}\right) = \left(\frac{1}{x}\right) + 3 \][/tex]
[tex]\[ g(f(x)) \neq \frac{1}{(x+3)^2} \][/tex]
Therefore, Option A is incorrect.
### Option B:
- [tex]\( f(x) = \frac{1}{x^2} \)[/tex]
- [tex]\( g(x) = x+3 \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g\left(\frac{1}{x^2}\right) = \left(\frac{1}{x^2}\right) + 3 \][/tex]
[tex]\[ g(f(x)) \neq \frac{1}{(x+3)^2} \][/tex]
Therefore, Option B is incorrect.
### Option C:
- [tex]\( f(x) = x^2 \)[/tex]
- [tex]\( g(x) = x+3 \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g\left(x^2\right) = \left(x^2\right) + 3 \][/tex]
[tex]\[ g(f(x)) \neq \frac{1}{(x+3)^2} \][/tex]
Therefore, Option C is incorrect.
### Option D:
- [tex]\( f(x) = x+3 \)[/tex]
- [tex]\( g(x) = \frac{1}{x^2} \)[/tex]
Applying these:
[tex]\[ g(f(x)) = g(x+3) = \frac{1}{(x+3)^2} \][/tex]
[tex]\[ g(f(x)) = \frac{1}{(x+3)^2} \][/tex]
This matches the given function [tex]\( h(x) \)[/tex].
Therefore, the correct possible decomposition of [tex]\( h(x) \)[/tex] is:
[tex]\[ \boxed{f(x) = x+3, \ g(x) = \frac{1}{x^2}} \][/tex]
The correct option is D.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.